Shari’ah supervisory board characteristics effects on Islamic banks’ performance: Evidence from Malaysia - Nomran, Naji; Haron, Razali; Hassan, Rusni (2016)
The performance of Shari’ah supervisory board continues to be a matter of concern especially for Islamic banks across countries that have a different regulatory environment. This study aims to examine the effects of Shari’ah supervisory board characteristics on Islamic banks’ performance using a sample of 15 Malaysian banks for the period from 2008 to 2015. Seven Shari’ah supervisory board characteristics were employed as explanatory variables which are the board size, cross-membership, doctoral qualification, reputation, experience, total change in the SSB composition and remuneration. By employing random-effects GLS and GMM method for a robustness check, it was found that five out of the seven explanatory variables have significant relationships with Islamic banks’ performance. These factors are SSB Size, SSB doctoral qualification, SSB reputation, total change in the SSB composition and SSB remuneration.